Relationship between heart rate and blood lactate responses to a sport specific field test in elite male and female badminton players. - Gaudet, Pierre. (University of Ottawa (Canada), 1990)
No statistically significant difference between genders was observed. Among all the comparisons of the 30 second intervals within the 5 minute HRREC data, only two time periods were not statistically significant. One was early in recovery and one was late in recovery. Mean BLa went down every minute from 6.91 mMol at post 1 minute to 6.51 mMol at post 5 minute but this difference was not statistically significant. No statistically significant correlation were found to exist between HRREC and BLaREC. However, PEAKBLa following the test was correlated with HRREC measurements such that the following two trends were found. First, the correlation between PEAKBLa and the absolute HR values obtained at different time intervals during recovery became stronger with increasing time up to the 2nd minute of recovery and second, PEAKBLa was negatively correlated with 5 minute HRREC. PEAKBLa was negatively correlated with the HRREC obtained in the first two minutes of recovery but this relation became positive between the 2nd and 5th minute of recovery. (Abstract shortened by UMI.)
Keywords: Biology, Animal Physiology.